Trabalho docente no ensino médio no Brasil: desafios à universalização com qualidade social - Gilvan Luiz Machado Costa (EccoS – Revista Científica)
The aim of this paper is to discuss issues related to the teacher work and secondary school enrollment, and they are intertwined with its universalization with social quality. For that purpose, the statistical information provided by the National Institute of Anisio Teixeira Educational Studies (INEP) is used to discuss enrollment issues, educational indicators and the work of teaching at high school. Based on discussions held, it highlights the goals related to the regular secondary school and teaching contained in the Draft Law No. 8035, as of 2010, establishing the National Education Plan. The results showed that the universalization of secondary education with social quality in Brazil presupposes a resumption of enrollment expansion and can only be achieved if teaching conditions are improved with the increase of scientific, social and economic status of the Brazilian basic education teachers.